Applications of artificial intelligence (AI) and machine learning (ML) in the petroleum industry - Shah, Manan (Manan Rajiv); Kshirsagar, Ameya; Panchal, Jainam (Boca Raton : CRC Press, 2023)
"Today, raw data on any industry is widely available. With the help of artificial intelligence and machine learning, this data can be used to gain meaningful insights. In addition, as data is the new raw material for today's world, artificial intelligence and machine learning will be applied in every industrial sector. Industry 4.0 mainly focuses on the automation of things. From that perspective, the oil and gas industry is one of the largest industries in terms of economy and energy. Applications of Artificial Intelligence and Machine Learning in the Petroleum Industry analyzes the use of artificial intelligence and machine learning in the oil and gas industry across all three sectors, namely upstream, midstream and downstream. It covers every aspect of the petroleum industry as related to the application of artificial intelligence and machine learning, ranging from exploration, data management, extraction, processing, real-time data analysis, monitoring, cloud-based connectivity system, conditions analysis to the final delivery of the product to the end customer, while taking into account the incorporation of the safety measures for a better operation and the efficient and effective execution of operations. The book explores the variety of applications that can be integrated to support the existing petroleum and adjacent sectors to solve industry problems. It will serve as a useful guide for professionals working in the petroleum industry, industrial engineers, artificial intelligence and machine learning experts and researchers, as well as students"--
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum engineering -- Data processing; Petroleum industry and trade -- Data processing; Gas industry -- Data processing; Artificial intelligence -- Industrial applications; Machine learning -- Industrial applications; TECHNOLOGY / General; TECHNOLOGY / Petroleum